Deciphering the pharmacological mechanisms of Chaenomeles Fructus against rheumatoid arthritis by integrating network pharmacology and experimental validation. Issue 10 (7th July 2022) - Sun, Mengjia; Zhao, Haijun; Liu, Yuecheng; Ma, Yanni; Tian, Zhenhua; Wang, Huanjun; Wei, Sheng; Guo, Qingmei; Gu, Zhengwei; Jiang, Haiqiang
Abstract: Chaenomeles Fructus is a plant that can be used for both food and medicine. Modern studies have shown that Chaenomeles Fructus has anti‐inflammatory and immunosuppressive effects on arthritis. However, the mechanism of action of Chaenomeles Fructus on rheumatoid arthritis (RA) and its main active ingredients are still unclear. This study was aimed at devising an integrated strategy for investigating the bioactivity constituents and possible pharmacological mechanisms of Chaenomeles Fructus against RA. The components of Chaenomeles Fructus were analyzed using UPLC‐Q‐Exactive orbitrap MS techniques and applied to screen the active components of Chaenomeles Fructus according to their oral bioavailability and drug‐likeness index. Then, we speculated on the potential molecular mechanisms of Chaenomeles Fructus against RA through a network pharmacology analysis. Finally, the potential molecular mechanisms of Chaenomeles Fructus against RA were validated in a complete Freund's adjuvant (CFA)‐induced RA rat model. We identified 48 components in Chaenomeles Fructus and screened seven bioactive ingredients. The results of the network pharmacology prediction and the experimental verification results were analyzed by Venn analysis, and the experimental results concluded that Chaenomeles Fructus mainly interferes with the inflammation of RA by inhibiting arachidonic acid metabolism and the MAPK signaling pathway. This study identified the ingredients of Chaenomeles Fructus by UPLC‐Q‐Exactive orbitrap MS and explained the possible mechanisms of Chaenomeles Fructus against RA by integrating network pharmacology and experimental validation. Abstract : Taking all the above results together, we identified 48 chemical components from Chaenomeles Fructus based on UPLC‐Q‐Exactive orbitrap MS, which mainly includes four types: amino acids, organic acids, flavonoids, and triterpenes. Moreover, we predicted the mechanism of action of Chaenomeles Fructus in the treatment of RA with network pharmacology and verified it through CFA‐induced RA in rats. The results of the network pharmacology prediction and the verification experimental results were analysed by Venn analysis, and the experimental results concluded that Chaenomeles Fructus mainly interferes with the inflammation of RA by inhibiting arachidonic acid metabolism and the MAPK signalling pathway.